On the Stability and Acceleration of Projection Algorithms - Maibed, Zena H.; Salem, Noor N. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
The focus of this paper is the presentation of a new type of mapping called projection Jungck zn- Suzuki generalized and also defining new algorithms of various types (one-step and two-step algorithms) (projection Jungck-normal N algorithm, projection Jungck-Picard algorithm, projection Jungck-Krasnoselskii algorithm, and projection Jungck-Thianwan algorithm). The convergence of these algorithms has been studied, and it was discovered that they all converge to a fixed point. Furthermore, using the previous three conditions for the lemma, we demonstrated that the difference between any two sequences is zero. These algorithms' stability was demonstrated using projection Jungck Suzuki generalized mapping. In contrast, the rate of convergence of these algorithms was demonstrated by contrasting the rates of convergence of the various algorithms, leading us to conclude that the projection Jungck-normal  algorithm is the fastest of all the algorithms mentioned above.